Eutrophication patterns in an eastern Mediterranean coastal lagoon: Vassova, Delta Nestos, Macedonia, Greece - ORFANIDIS, S.; STAMATIS, N.; RAGIAS, V.; SCHRAMM, W. (Mediterranean Marine Science, 2005)
The results of an intensive monitoring study of main eutrophication parameters in relation to fish farming management, climate and hydrography in the Vassova coastal lagoon (Nestos Delta) are presented. The overall aim is to produce basic knowledge in order to contribute to the management of eutrophication of coastal lagoons at local and national levels. Due to extensive spatiotemporal variability of the measured parameters correlation and regression polynomial analysis was used to identify patterns (p<0.05). Freshwater was the main source of nitrate and phosphate in the lagoon. This finding has justified the reduction of freshwater inflow in the past, which, however, has increased mean salinity to 30 PSU and reduced spatial salinity gradients. Maximum nitrate values in winter coincided with adverse climatic and hydrographic conditions (high precipitation, strong NE to E winds and low tide) and fish farming management that hinder water circulation. Dissolved phosphorus variability indicated the combination of the external (freshwaters) and internal (sediment) P-sources. N/P water values indicated nitrogen being the most important nutrient for primary producers throughout the year, except in winter, when phosphorus was the most important nutrient. Practical measures for improving fish farming practices to decrease “eutrophication risk” during winter are suggested. Existing nutrient data from the Vassova and from other Greek lagoons in comparison were also presented and discussed.